Energetic properties of rectangular sound sources with large directionality - Puch, Andrzej (Archives of Acoustics, 1987)
In this paper the author investigated energetic properties of rectangular sound sources with the following amplitude distributions of the vibration velocity: uniform, HAmmiNG’s, HANNING’S and BLACKMAN’S. The frequency characteristics of the active power, reactive power and apparent power of these sources was determined, as well as their power factor. It was found that sources under investigations effectively radiate vibration energy into the far field (i.e. with the power factor equal to one) in the wave length range, in which they exhibit large directionality. The energy of vibrations radiated by a source into the far field in a unit of time is by an order of magnitude smaller in the case of HAMMING’S, HANNING’S and BLACKMAN’S distributions than in the case of a uniform distribution. Therefore, an increase of the directivity of radiation of the vibration energy into the far field by rectangular sound sources is accompanied by a decrease of the value of radiated energy.